Microbial production of keratinase from Bacillus velezensis strain MAMA: A novel enzyme for eco-friendly degradation of keratin waste - Aimon Khan; Kashif Mehmood; Akhtar Nadhman; Sami Ullah Khan; Aamer Ali Shah; Ziaullah Shah (Heliyon, 2024)
Keratin waste has become an increasingly serious environmental and health hazard. Keratin waste is mainly composed of keratin protein, which is one of the most difficult polymers to break down in nature and is resistant to many physical, chemical, and biological agents. With physical and chemical methods being environment damaging and costly, microbial degradation of keratin using keratinase enzyme is of great significance as it is both environment friendly and cost-effective. The aim of this study was to extract and purify keratinase from bacterial species isolated from the soil. Among the organisms, an isolate of Bacillus velezensis, coded as MAMA could break down chicken feathers within 72 hours (h). The isolated strain produced significant levels of keratinase in mineral salt medium by supplying chicken feathers as the sole source of nitrogen and carbon. Feather deterioration was observed with the naked eye, and enzyme activity was evaluated using a spectrophotometric assay. Sodium dodecyl-sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and zymography results revealed that the keratinase protein produced by Bacillus velezensis had a molecular weight between 40 and 55 kilodalton (kDa).